DIGITAL MEDIA: PENGGUNAANNYA DALAM PROSES KONSTRUKSI BRANDING WISATA HALAL “THE LIGHT OF ACEH” - Husniati, Ade Muana; Lubis, Suwardi; Yusnadi, Yusnadi (Interaksi: Jurnal Ilmu Komunikasi, 2024)
This research aims to analyze the branding process in constructing the halal tourism destination of Aceh Province as "the light of Aceh". Using a constructivist paradigm and qualitative approach, this study collects data through in-depth interviews with the publication team and the Aceh halal tourism acceleration team at the Aceh Culture and Tourism Office. The research findings reveal that the marketing communication efforts carried out by the Aceh Culture and Tourism Office in constructing the brand image of halal tourism destinations based on the first stage of media construction are to prepare construction materials in collaboration with relevant publics, namely the publication team, the Aceh halal tourism acceleration team, and other tourism associations and communities. The second stage is the stage of construction distribution through various media and channels, especially social media. In the use of digital media, the concrete concept is real-time. The third stage is the stage of construction formation, namely the construction of the image constructed by the Aceh Culture and Tourism Office through the media used, especially owned/shared/social media, is the good news model. The fourth stage, namely the confirmation stage, is evident in the adoption of the logo by various publics. Other confirmations are that in the same year when the halal tourism destination brand was launched in 2016 to 2022, Aceh received both national and international awards.